2018
DOI: 10.1111/imj.13667
|View full text |Cite
|
Sign up to set email alerts
|

Underappreciation of non‐alcoholic fatty liver disease by primary care clinicians: limited awareness of surrogate markers of fibrosis

Abstract: Our findings demonstrate that many primary care clinicians underestimate the prevalence of NAFLD and under-recognise the clinical spectrum of NAFLD and how this is assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
80
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 28 publications
4
80
2
Order By: Relevance
“…Although not usually specified in the referral letter, we presume that the presence of abnormal liver enzymes was identified during routine clinical investigations (i.e., monitoring of diabetes) or performed for a specific clinical indication (i.e., presence of steatosis or hepatomegaly on ultrasound or abdominal pain). The findings support an earlier study in which most of the PCPs surveyed (70.6%) said they were unlikely to refer a patient with NAFLD for a hepatology opinion unless the liver function tests were abnormal . This approach in selecting patients for referral based on elevated aminotransferases may fail to identify patients with significant liver disease, as most people with NAFLD have traditional normal‐range liver blood tests, and liver enzyme levels do not reflect the presence or severity of fibrosis .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Although not usually specified in the referral letter, we presume that the presence of abnormal liver enzymes was identified during routine clinical investigations (i.e., monitoring of diabetes) or performed for a specific clinical indication (i.e., presence of steatosis or hepatomegaly on ultrasound or abdominal pain). The findings support an earlier study in which most of the PCPs surveyed (70.6%) said they were unlikely to refer a patient with NAFLD for a hepatology opinion unless the liver function tests were abnormal . This approach in selecting patients for referral based on elevated aminotransferases may fail to identify patients with significant liver disease, as most people with NAFLD have traditional normal‐range liver blood tests, and liver enzyme levels do not reflect the presence or severity of fibrosis .…”
Section: Discussionsupporting
confidence: 66%
“…We and others have shown that PCPs often underestimate the prevalence of NAFLD, and this may contribute to many affected individuals remaining undiagnosed, in part because the condition is usually asymptomatic and associated with relatively normal or only mildly elevated liver enzyme levels. PCPs are often not familiar with the clinical spectrum of NAFLD and how this is assessed using fibrosis biomarkers and algorithms .…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Although NAFLD screening in the community is not currently recommended, European clinical practice guidelines advise that “… the progressive form of NAFLD (non‐alcoholic steatohepatitis (NASH)), particularly when associated with advanced fibrosis, should be identified in patients at risk (age >50 years, T2DM or metabolic syndrome (MetS)), because of its prognostic implications.” Primary care clinicians and hospital specialists other than gastroenterologists and hepatologists have a key role in identifying patients with NAFLD at risk of significant liver disease who may require specialist referral for further evaluation or who need closer management of metabolic comorbidities and lifestyle interventions. However, many primary care clinicians and hospital specialists underestimate the prevalence and do not fully recognize the clinical spectrum of NAFLD and how this is assessed …”
mentioning
confidence: 99%
“…Powell et al have reported in the Internal Medicine Journal and commented about the lack of awareness of non‐alcoholic forms of fatty liver disease in Australia by those in general practice and by other medical specialties in Brisbane . We do not know whether healthcare professionals in the Capital Region, especially including primary care and diabetes services, are more aware of the potential significance of this common disorder than their Melbourne or Brisbane counterparts.…”
mentioning
confidence: 98%